2009
DOI: 10.1111/j.1574-6968.2009.01785.x
|View full text |Cite
|
Sign up to set email alerts
|

The F1FOATP synthase genes inMethanosarcina acetivoransare dispensable for growth and ATP synthesis

Abstract: There is a long-standing discussion in the literature, based on biochemical and genomic data, whether some archaeal species may have two structurally and functionally distinct ATP synthases in one cell: the archaeal A(1)A(O) together with the bacterial F(1)F(O) ATP synthase. To address a potential role of the bacterial F(1)F(O) ATP synthase, we have exchanged the F(1)F(O) ATPase gene cluster in Methanosarcina acetivorans against a puromycin resistance cassette. Interestingly, the mutant was able to grow with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
(33 reference statements)
6
13
0
Order By: Relevance
“…S6). This showed that N-ATPase contains at least part of the δ-subunit, in agreement with the earlier analyses (Saum et al , 2009). …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…S6). This showed that N-ATPase contains at least part of the δ-subunit, in agreement with the earlier analyses (Saum et al , 2009). …”
Section: Resultssupporting
confidence: 93%
“…S1). As has been noted previously (Meier et al , 2009; Saum et al , 2009), this Glu residue could potentially provide two ligands for the Na + ion and thereby complete the Na + coordination shell. If so, all these N-ATPases would end up being capable of binding Na + ions.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although it is conceivable that the atp -type genes may be significantly expressed under unknown growth conditions, an alternative possibility is that they constitute a "dead-ended" lateral gene transfer event [23]. Interestingly, the deletion of the atp gene region of M. acetivorans conferred no phenotype [25]. The atpX gene present in the M. acetivorans and M. barkeri genomes is conserved in some, but not all bacterial-like ATP synthase operons.…”
Section: Discussionmentioning
confidence: 99%
“…One notable exception is Methanosarcina acetivorans, which has genes for both F-type and A-type ATP synthases. Saum et al (56) have recently shown that the F-type ATP synthase is not essential for the growth of M. acetivorans. The M. ruminantium M1 genome contains an ahaHIKECFABD operon, and no genes for an F-type enzyme were identified.…”
Section: Discussionmentioning
confidence: 99%